Bunch-by-bunch profile diagnostics in storage rings by infrared array detection. (21st July 2015) - Drago, A; Bocci, A; Cestelli Guidi, M; De Sio, A; Pace, E; Marcelli, A
Abstract: The latest generation of storage rings, both light sources and colliders, needs improved diagnostics systems to achieve the challenging design parameters. Although many commercially available diagnostics can be used to characterize performance in real time, modern high-luminosity and low-emittance accelerators need much more sophisticated and sensitive diagnostics devices. DAΦNE (Double Annular Φ-Factory for Nice Experiments), the LNF (Laboratori Nazionali di Frascati) e + /e − Φ-factory, is a collider working at an energy of 1.02 GeV in the centre of mass. The existing luminosity diagnostics at DAΦNE cannot explain the 30% discrepancy between the extrapolated 10-bunch peak luminosity and the standard fill pattern made by colliding 100 bunches. Ruling out the presence of nonlinear contributions and/or saturation of the existing KLOE (Kaon Long Experiment) detector when used as a precision luminosity monitor, new diagnostic approaches are needed. Here we describe the technique that we introduced at DAΦNE based on multi-pixel time-resolved infrared detectors. Preliminary results are presented and discussed.